2018
DOI: 10.1021/acs.jpcc.8b04640
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Induced Evolution of “Ge(OH)2”: Controlling the Formation of Oxide-Embedded Ge Nanocrystals

Abstract: Germanium nanocrystals (GeNCs) hold great promise as active materials in many applications including solar cells, biological imaging, Bragg reflectors, light-emitting diodes, and nonvolatile memory devices. However, because of the size-, shape-, and composition-dependent nature of their properties, it is essential that methods affording high-purity, well-defined GeNCs be developed. Herein, we report a systematic investigation of a series of “Ge­(OH)2” precursors using X-ray diffraction, X-ray photoelectron spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 62 publications
1
14
0
1
Order By: Relevance
“…The surrounding matrix remains too broadened to detect. [218] For halogen-containing inorganic germanium compounds, 73 Ge experimental NMR data and GIPAW DFT calculations were reported from GeX 4 and GeX 2 germanium halides and revealed a wide range of C Q of 0.16 to 35 MHz (Table 9). [219] For the GeX 4 series δ iso could be correlated with the halide electronegativity.…”
Section: Compoundmentioning
confidence: 99%
“…The surrounding matrix remains too broadened to detect. [218] For halogen-containing inorganic germanium compounds, 73 Ge experimental NMR data and GIPAW DFT calculations were reported from GeX 4 and GeX 2 germanium halides and revealed a wide range of C Q of 0.16 to 35 MHz (Table 9). [219] For the GeX 4 series δ iso could be correlated with the halide electronegativity.…”
Section: Compoundmentioning
confidence: 99%
“…The XRD pattern of the hydrolyzed GeCl 2 Ádioxane (prior to annealing) exhibits broad amorphous features centered around 31.41 and 50.81 2y. Previous studies from Javadi et al 24,25 and Sun et al 23 also reported amorphous features from GeO 2 -derived GeO prior to annealing; however these amorphous scattering features were at slightly lower angles (27.51 and 501 2y) and were attributed to amorphous germanium. 24,25 The different positions of the amorphous features in the precursors indicate that our samples may possess a different composition from the previous studies.…”
mentioning
confidence: 83%
“…Previous studies from Javadi et al 24,25 and Sun et al 23 also reported amorphous features from GeO 2 -derived GeO prior to annealing; however these amorphous scattering features were at slightly lower angles (27.51 and 501 2y) and were attributed to amorphous germanium. 24,25 The different positions of the amorphous features in the precursors indicate that our samples may possess a different composition from the previous studies. Differential scanning calorimetry (DSC) reveals an exotherm that we hypothesized to coincide with the decomposition of the precursor and formation of Ge nuclei around 250 1C (Fig.…”
mentioning
confidence: 83%
See 2 more Smart Citations